Skrining Pemeriksaan Gula Darah, Asam Urat, serta Kolesterol sebagai Upaya Pencegahan Penyakit Metabolik pada Usia Produktif - Krisdianilo, Visensius; Felicia Lubis , Agnes; Haiti, Margareta; Sudarmi, Lusia; Septie Ch, Lidwina (Jurnal Ragam Pengabdian, 2026)
Metabolic syndrome is a cluster of cardiometabolic risk factors that increase the risk of developing chronic conditions, including type 2 diabetes mellitus and cardiovascular disease. However, many patients or members of the general public are unaware of these conditions, compounded by issues such as low awareness of the importance of routine health check-ups, particularly laboratory tests for early detection of this metabolic disease. The purpose of this community service activity was to screen blood sugar, uric acid, and cholesterol levels, accompanied by health education as a preventive and promotive measure for the productive age group. The outreach activity was conducted with 38 teachers and education staff at Xaverius 2 Senior High School in Palembang. Its implementation involved several stages: preparation, execution, and evaluation. The results showed that 15 respondents had normal blood pressure, while 23 individuals had hypertension. Regarding cholesterol levels, 14 respondents had cholesterol levels ≥ 200 mg/dL, 4 had uric acid levels ≥ 7.2 mg/dL, and 3 had blood sugar levels > 150 mg/dL.